Hybrid-Discovery Learning: Enhancing Critical Thinking Skills and Learning Outcomes in Science and Social Studies among Elementary Students - Mufidah, Lukluk Nur; Purwowidodo, Agus (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The objective of this research is to investigate the influence of Hybrid-Discovery Learning (Hybrid-DL) implementation on students' critical thinking abilities and performance. This study uses field research with a quantitative approach, and the Post-test Only Control-Group Quasi-Experiment method was employed. The study population comprised 54 fifth-grade students from Bayanul Azhar Bendiljati Kulon Sumbergempol Islamic Elementary School, divided into three classes: V-A (16 students), V-B (15 students), and V-C (23 students). Data collection instruments included learning outcome test sheets and critical thinking skills record tests. Data collection techniques used in this study were 1) Observation, researchers conducted observations of the learning process taking place at Bayanul Azhar Bendiljati Kulon Sumbergempol Islamic Elementary School; 2) Interview, researchers conducted interviews with teachers who teach science subjects to see the development of students' critical thinking after applying the Hybrid-Discovery learning model. The obtained data were analysed using a two-way MANOVA analysis, with a significance level of 5%. The research findings show that Hybrid-DL has a significant effect on the achievement of critical thinking skills and learning outcomes. This effect is demonstrated by the improvement in student learning outcomes in the form of learning motivation in the form of increased student enthusiasm for learning as evidenced by increased learning motivation questionnaire scores, and learning achievement as represented by increased student formative assessment scores in the form of report card grades, as well as increased student critical thinking skills as taken from improved critical thinking skills test results.